An investigation of the patterns and outcomes of Electroencephalographic (EEG) recording requests in the management of neuropsychiatric disorders in a teaching Hospital in Nigeria - Ajiboye, Peter Omoniyi (Afr Health Sci, 2017)
OBJECTIVE: To evaluate the relevance of Electroencephalography (EEG) in the management of various neuropsychiatric conditions in University of Ilorin Teaching Hospital (UITH), Ilorin. BACKGROUND: EEG is still relevant in the diagnosis and management of patients with seizure disorders and extends to other neuropsychiatric conditions. However, very few studies have examined the use of EEG in developing countries, including Nigeria. METHODS: The EEG records of 154 patients between January 2012 and December 2012 were reviewed. EEG unit's records, including EEG request forms and EEG reports were examined. Socio demographic data, clinical data and the neurologist's comments on the EEG recordings were extracted and recorded on the proforma form. RESULTS: A total of 142(92.2%) of the patients out of 154 had complete records and were studied. Majority (84.5%) of the patients were below the age of 30 years. Various types of seizure disorders accounted for 80% of the provisional diagnosis. The EEG diagnosis based on the interpretation of the EEG records showed that 96 (67.6%) of the patients had normal records. CONCLUSION: EEG still plays a very important role in the investigation of neuropsychiatric conditions especially epilepsy in developing countries. EEG facilities should be readily available.